KAJIAN REKLAMASI LAHAN DAERAH ALIRAN SUNGAI BATANG KURANJI KOTA PADANG (JURNAL SPASIAL, 2014)
Reclamation activities aimed at fixing or setting up a land use that is disturbed as a result of business activities penggolahan inappropriate environment, in order to function and useful for their designated purpose. This study aims to determine land use (DAS) Kuranji Batang Padang city, and the direction of land reclamation in the watershed (DAS) Kuranji Batang Padang. Tutorial reklamsi done on land along the streams of the river is, with methods of soil conservation by means of agronomic or vegetative, mechanical and chemical.Keywords: watershed, land use, land reclamation landing